Christianity's first steps into its third millennium - Grundmann, Christoffer H. (International review of mission, 2005)
1Christoffer H. Grundmann is the John R, Eckrich University Professor in Religion and the Healing Arts at Valparaiso University, Valparaiso, Indiana, USA Abstract This solicited article reflects on two major ecumenical events marking the first steps of Christianity into its third millennium. The first is the CWME Conference held at Athens, May 9–16, 2005, the second is the ninth Assembly of the WCC at Porto Alegre, Brazil, February 14–23, 2006. The introduction begins with the symbol-laden opening ceremony of the Athens Conference where a huge cross shipped from Jerusalem was received, a cross, which also will be referred to in Porto Alegre. This provided a telling image about Christianity along its way from local to global significance. The article first reviews the Athens conference in light of ecumenical innovations. These include the genuine embrace of a larger ecumenical community than just the WCC membership and an appeal to the basic commonalities of Christian life beyond dogmatic constraints by turning to Bible-study and prayer. The same perspective also informs the second part of the article, which looks at the forthcoming Assembly and points to some significant changes such as giving up the majority vote in favor of a “consensus model” and embedding the discussion of hot topics within the larger framework of “ecumenical conversations”. While these changes reflect an ecumenical maturity they are also bold and risky steps, which deserve to be regarded with appreciation and care. They are held to be expressions of a new spirit, bringing the church more truly in line with the kenotic love of God in Christ, something regarded as most telling about Christianity's self-perception upon entering its third millennium.